The place of philosophy of education in between theory and practice: Considerations on the last challenges of analytical philosophy and continental philosophy - Khosrow Bāgheri (فصلنامه نوآوری‌های آموزشی, 2006)
The last challenge on the place of philosophy of education was the discussion between Wilfred Carr, as a defender of continental philosophy, and Paul Hirst, as an outstanding representative of analytic philosophy, in 2005. Preparing the background for supporting practical philosophy against the theoretical one, Carr holds that philosophy of education should be considered as a branch of practical philosophy in order to both overcoming theory/practice gap and destroying the supposed security of philosophy of education against practical changes. In rejection of this conception, Hirst holds that the phrase of “practical philosophy” involves a misunderstanding because philosophy has always been an abstract and theoretical activity. According to him, philosophy is a second-order activity because its work, being verification of rational validity of beliefs and actions, presupposes the existence of beliefs and actions. Thus, the role of philosophy of education in verifying educational action is fulfilled indirectly through analyzing the concepts relevant to the action. It should be said in evaluating the two views that both of them are held in a reductive manner. Hirst takes theoretical reason as his main concern as Carr takes the same position on practical reason but it still seems better to keep the two reasons diverse and plural. If it is followed from Carr’s views that any division in philosophy or reason to theoretical and practical parts lead us to trap of theory/practice gap, then evidently it will not be acceptable. On the other hand, he is right to claim that philosophy of education in its theoretical feature provides a kind of security and absoluteness for itself that should be eliminated by a constant study on its historical limitations.